Effect of additional "clean" feeding on 90Sr and 137Cs content in prussian carp (Carassius gibelio) in the Chornobyl exclusion zone - O. V. Kashparova; S. Ye. Levchuk; M. O. Hrechaniuk; I. M. Gudkov; V. O. Kashparov (Âderna Fìzika ta Energetika, 2021)
Under natural conditions, in one of the most radioactively contaminated water bodies of the Chornobyl exclusion zone, lake Glyboke in 2020, experimental studies were carried out to assess the effectiveness of the use of additional "clean" feeding to reduce the levels of radioactive contamination of 90Sr and 137Cs in fish. The radiological efficiency of decreasing the 137Cs intake into the muscle tissue of fish with the use of additional "clean" feeding, mainly due to biological dilution, was 2.9 ± 0.4 times. The biological half-life of 137Cs in the muscle tissue of radioactively contaminated fish was 115 ± 25 days with the consumption of natural and additional "clean" food, which is approximately 2 times longer compared to the case when the fish consumes only clean food. In contrast to 137Cs, using additional "clean" feeding led to an increase of 90Sr content in the fish organism as compared to the control (up to 5 times) in proportion to the relative increase in the mass of fishbone tissue, which contains the bulk of strontium.